2022
DOI: 10.3390/plants11243564
|View full text |Cite
|
Sign up to set email alerts
|

Soil Acidification in Nutrient-Enriched Soils Reduces the Growth, Nutrient Concentrations, and Nitrogen-Use Efficiencies of Vachellia sieberiana (DC.) Kyal. & Boatwr Saplings

Abstract: Nitrogen (N) and phosphorus (P) nutrient enrichment is important for grasslands. This study aimed to determine how soils enriched with N and P influenced soil concentration correlations and affected the growth kinetics, mineral nutrition, and nitrogen-use efficiencies of Vachellia sieberiana grown in a greenhouse experiment. The soils used as the growth substrate were analysed and showed extreme acidity (low soil pH, 3.9). Nitrogen-enriched soils were more acidic than P-enriched soils. Exchangeable acidity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…and Mn 2+ concentrations indicate soil acidity problem in the area. These findings are in agreement with those of Zama et al [44] who reported an increase in soil acidity due to the toxicity effects of Al 3+ , Mn 2+ and Fe 2+ . They concluded that soil pH has a significant effect on plant growth and agricultural productivity.…”
Section: +supporting
confidence: 93%
“…and Mn 2+ concentrations indicate soil acidity problem in the area. These findings are in agreement with those of Zama et al [44] who reported an increase in soil acidity due to the toxicity effects of Al 3+ , Mn 2+ and Fe 2+ . They concluded that soil pH has a significant effect on plant growth and agricultural productivity.…”
Section: +supporting
confidence: 93%
“…Base saturation was positively correlated with soil pH (0.790, p < 0.01, Table S3) [41]. In general, when the soil pH is lowered, the concentration of exchangeable aluminum increases, which is known to be a toxic substance that inhibits root development and plant growth by interrupting the absorption and movement of nutrients [42][43][44]. Additionally, high soil organic matter content increases crop productivity by enhancing nitrogen absorption in plants through nitrogen mineralization [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…BS had a positive correlation with soil pH (0.684, p < 0.000, Table S5, Figure 2). Generally, when the pH of the soil decreases, the concentration of exchangeable aluminum increases, which is known as a toxic substance that inhibits root development and plant growth by interfering with the absorption and movement of nutrients [23][24][25]. In addition, high soil OM improves nitrogen absorption in plants through nitrogen mineralization, increasing crop productivity [26,27].…”
Section: Discussionmentioning
confidence: 99%